Utilizing virtual and augmented reality for educational and clinical enhancements in neurosurgery. (January 2017) - Pelargos, Panayiotis E.; Nagasawa, Daniel T.; Lagman, Carlito; Tenn, Stephen; Demos, Joanna V.; Lee, Seung J.; Bui, Timothy T.; Barnette, Natalie E.; Bhatt, Nikhilesh S.; Ung, Nolan; Bari, Ausaf; Martin, Neil A.; et al.
Highlights: Virtual reality (VR) and augmented reality (AR) have great potential in neurosurgery. Immersive VR has the potential to be used an educational tool. AR has the added potential of use in the live operative field. Further improvement of VR and AR is crucial to its integration into neurosurgery. Abstract: Neurosurgery has undergone a technological revolution over the past several decades, from trephination to image-guided navigation. Advancements in virtual reality (VR) and augmented reality (AR) represent some of the newest modalities being integrated into neurosurgical practice and resident education. In this review, we present a historical perspective of the development of VR and AR technologies, analyze its current uses, and discuss its emerging applications in the field of neurosurgery.